THE RELATIONSHIP OF GESTATIONAL DIABETES MELLITUS WITH PREECLAMSIA AND NEONATAL OUTCOME AT MOJOWARNO CHRISTIAN HOSPITAL - Dwi Safitri, Nimas Pristiwanto (Universitas HKBP Nommensen, 2022)
Background: GDM is one of the leading causes of maternal and infant morbidity and mortality worldwide. Riskesdas noted that the prevalence of diabetes mellitus in 2018 was 8.5%. GDM affects the mother in the form of weight gain, preeclampsia, eclampsia, cardiovascular complications, cesarean section, and maternal death, while in the fetus there can be birth injury, neonatal hyperbilirubinemia, hypoglycemia, idiopathic respiratory distress syndrome, and perinatal death. Objective: The purpose of this study was to determine the relationship between GDM and the incidence of preeclampsia along with neonatal outcomes and maternal complications in RSK. Mojowarno in 2020. Methods: This study uses a case-control approach that is processed using the chi-square statistical test method. The total sample of the study was 30 pregnant women with 15 people in each group. Results: The results of this study indicate that the relationship between GDM and preeclampsia (p = 0.028), for the relationship between GDM and maternal complications such as heart failure (p = 1,000), pulmonary edema (p = 1,000), eclampsia (p = 0.283), maternal mortality (p = <0.001), IUGR (p = 0.543), IUFD (p = 0.309), and for the relationship of GDM with neonatal complications in the form of low birth weight (p = 0.195), macrosomia birth (p = 0.032), and birth asphyxia (p = 0.031), stillbirth (p = 0.143). Conclusion: It can be concluded that there is a relationship between GDM and the incidence of preeclampsia, there is no relationship between GDM and maternal complications, and there is a relationship between GDM and neonatal outcomes in the form of macrosomia and asphyxia in RSK. Mojowarno in 2020. Keywords: diabetes mellitus, preeclampsia, maternal complications, neonatal outcomes